Оцінка можливості використання вентильно-реактивного двигуна у складі верстат-гойдалки - Мазуренко, Леонід Іванович; Бібік, Олена Василівна; Клименко, Вікторія Григорівна; Шихненко, Максим Олегович (НТУ "ХПІ", 2017)
Розроблено імітаційну модель приводу верстат-гойдалки на основі вентильно–реактивного двигуна (ВРД) з врахуванням періодичного навантаження. Момент навантаження на кривошипі верстат-гойдалки в залежності від кута його повороту розрахований графо-аналітичним методом. За результатами досліджень електромеханічних процесів ВРД визначено раціональні способи регулювання частоти обертання ротора, які забезпечують стабілізацію частоти обертання кривошипа та енергоефективність приводу верстат-гойдалки.

A simulation model of the machine-rocking chair based on the switched reluctance motor is developed taking into account the periodic load. The load torque at the crank of the machine-rocking chair, depending on the angle of its rotation, is calculated graphical-nalytical method. According to the research of electromechanical processes of the SRM defined the rational methods of the rotor speed control, which provide a range of stabilization of the crank speed, and the efficiency of the machine-rocking chair drive energy. The possibility of applying the SRM as a drive for the machine-rocking chair on the basis of technological requirements is estimated.
Evaluation of the use of switched reluctance motors in the machine-rocking chair unit
Keywords: імітаційна модель; двигун; частота обертання; регулювання; енергоефективність; switched reluctance motor; machine-rocking chair; engine speed; simulation model adjustment; stabilization; energy efficiency